EMBRACE - Spevak, Aimee (MD Conference Express, 2015)
Treatment with bendavia in patients receiving percutaneous coronary intervention for STEMI in the EMBRACE STEMI trial did not result in a reduction in reperfusion injury-related outcomes compared with placebo. However, these data have led to further hypotheses, which are currently under investigation in clinical trials.